Erwinia wuhanensis sp. nov. isolated from human blood - Zhang, Yingmiao; Zhan, Yu; Yang, Jing; Lu, Zhongxin (Frontiers in Microbiology, 2025)
IntroductionA novel Erwinia strain, BC051422T, was isolated from the blood of a patient at the Central Hospital of Wuhan, Wuhan, PR China, in 2022. The strain was identified as gram-negative, facultatively anaerobic, motile, and rod-shaped.MethodsPreliminary analysis based on the 16S rRNA gene sequence and multilocus sequence analysis of the atpD, infB, rpoB, and gyrB genes unveiled that this strain is closely related to Erwinia members. Whole-genome sequencing was performed, and the average nucleotide identity (ANI) and in silico DNA–DNA hybridization (isDDH) values between strain BC051422T and type strains of all known Erwiniaceae species ranged from 68.8% to 83.4% and 19.2% to 35.5%, respectively, which below the accepted species delineation thresholds of 95% for ANI and 70% for isDDH. The major cellular fatty acids of strain BC051422T were C16:0, C16:1 ω7c/C16:1 ω6c, and C17:0 cyclo, consistent with profiles similar to those observed in other Erwinia species. The genomic DNA G+C content was 55.95 mol%. Strain BC051422T can be differentiated from other Erwinia species by its ability to ferment sucrose, but its inability to metabolize mannose, rhamnose, melibiose, and sorbitol.ResultsGenotypic and phenotypic characteristics together support the classification of strain BC051422T as a novel species of the genus Erwinia, for which the name Erwinia wuhanensis sp. nov. is proposed. The type strain of E. wuhanensis sp. nov. is BC051422T (=GDMCC 1.4074T = JCM 36319T).